Future directions in oil spill modeling - Tor Nordam; Ana J. Abascal; Germán Aragón; Hossein Babaei; Christopher H. Barker; Kuo-Hsien Chang; Knut-Frode Dagestad; Rodrigo Duran; Deborah French-McCay; Melissa Gloekler; Aurelien Hospital; Panagiota Keramea; et al. (Ocean Modelling, 2026)

Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The learning efficiency of the ant Anoplolepis gracilipes (Hymenoptera: Formicidae) varies with temperature - C.-H. Chan; T.-S. Lin; H.-D. Lin; C.-I. Chiu (Insectes Sociaux, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Association between blood nicotinamide adenine dinucleotide levels and blood laboratory parameters at baseline and after nicotinamide mononucleotide supplementation in middle-aged healthy individuals: post hoc analysis of a randomized, double-blinded, placebo-controlled clinical trial - Ajla H. Kuerec; Weilan Wang; Keona D. M. Fokke; Lin Yi; Zhigang Lin; Aditi Vaidya; Sohal Pendse; Sornaraja Thasma; Niranjan Andhalkar; Ganesh Avhad; Vidyadhar Kumbhar; Andrea B. Maier (GeroScience, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Landsat 8 OLI atmospheric correction neural network for inland waters in tropical regions - M. Van Nguyen; O. T. La; H. T. T. Nguyen; D. Heriza; B.-Y. Lin; G. Y. I. Ryadi; Chao-Hung Lin; Vinh Quang Pham (International Journal of Environmental Science and Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Effects of the organochlorine pesticide metabolite p,p’-DDE on the gastrointestinal lipidome in fish: A novel toxicity pathway for a legacy pollutant - Alexis M. Wormington; David J. Gabrielli; Mohammad-Zaman Nouri; Ashley M. Lin; Sarah E. Robinson; John A. Bowden; Nancy D. Denslow; Tara Sabo-Attwood; Joseph H. Bisesi (Environmental Pollution, 2024)

Outdoor physical activity is not associated with better mental health in a sample of predominantly Black people, but spending time in parks is - Amber L. Pearson; Wei Liu; Zihan Lin; Teresa H. Horton; Jennifer D. Roberts; Tim Chambers; Ashton Shortridge; Karin A. Pfeiffer; Joseph Gardiner (Urban Forestry & Urban Greening, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

Telomere dynamics during hibernation in a tropical primate - M. B. Blanco; D. L. Smith; L. K. Greene; A. D. Yoder; E. E. Ehmke; J. Lin; P. H. Klopfer (Journal of Comparative Physiology B, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

The effect of polychlorinated biphenyls extracted from offshore sediments on the intestinal epithelium and microflora of zebrafish - M. Zhang; D-H Zhu; Q-L Song; M-M Chen; Y Hu; D-J Kang; Z-B Chen; H-Y Lin; F-H Nie; J-J Chen (International Journal of Environmental Science and Technology, 2023)

Cloud condensation nuclei activation properties of Mediterranean pollen types considering organic chemical composition and surface tension effects - A. Casans; F. Rejano; J. Maldonado-Valderrama; J.A. Casquero-Vera; S. Ruiz-Peñuela; B.L. van Drooge; H. Lyamani; A. Cazorla; E. Andrews; Jack J. Lin; F. Mirza-Montoro; D. Pérez-Ramírez; et al. (Atmospheric Environment, 2023)

Solubility controls on plutonium and americium release in subsurface environments exposed to acidic processing wastes - Hilary P. Emerson; Sergey I. Sinkov; Carolyn I. Pearce; Kirk J. Cantrell; Calvin H. Delegard; Michelle M.V. Snyder; May-Lin Thomas; Dallas D. Reilly; Edgar C. Buck; Lucas E. Sweet; Amanda J. Casella; Jennifer C. Carter; et al. (Applied Geochemistry, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

A bibliometric review of peripartum cardiomyopathy compared to other cardiomyopathies using artificial intelligence and machine learning - M. Grosser; H. Lin; M. Wu; Y. Zhang; S. Tipper; D. Venter; J. Lu; C. G. dos Remedios (Biophysical Reviews, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

From zero to infinity: Minimum to maximum diversity of the planet by spatio‐parametric Rao’s quadratic entropy - Duccio Rocchini; Matteo Marcantonio; Daniele Da Re; Giovanni Bacaro; Enrico Feoli; Giles M. Foody; Reinhard Furrer; Ryan J. Harrigan; David Kleijn; Martina Iannacito; Jonathan Lenoir; Meixi Lin; et al. (Global Ecology and Biogeography, 2021)
Aim The majority of work done to gather information on the Earth's biodiversity has been carried out using in‐situ data, with known issues related to epistemology (e.g., species determination and taxonomy), spatial uncertainty, logistics (time and costs), among others. An alternative way to gather information about spatial ecosystem variability is the use of satellite remote sensing. It works as a powerful tool for attaining rapid and standardized information. Several metrics used to calculate remotely sensed diversity of ecosystems are based on Shannon’s information theory, namely on the differences in relative abundance of pixel reflectances in a certain area. Additional metrics like the Rao’s quadratic entropy allow the use of spectral distance beside abundance, but they are point descriptors of diversity, that is they can account only for a part of the whole diversity continuum. The aim of this paper is thus to generalize the Rao’s quadratic entropy by proposing its parameterization for the first time. Innovation The parametric Rao’s quadratic entropy, coded in R, (a) allows the representation of the whole continuum of potential diversity indices in one formula, and (b) starting from the Rao’s quadratic entropy, allows the explicit use of distances among pixel reflectance values, together with relative abundances. Main conclusions The proposed unifying measure is an integration between abundance‐ and distance‐based algorithms to map the continuum of diversity given a satellite image at any spatial scale. Being part of the rasterdiv R package, the proposed method is expected to ensure high robustness and reproducibility.

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

Modeling motor task activation from resting-state fMRI using machine learning in individual subjects - Chen Niu; Alexander D. Cohen; Xin Wen; Ziyi Chen; Pan Lin; Xin Liu; Bjoern H. Menze; Benedikt Wiestler; Yang Wang; Ming Zhang (Brain Imaging and Behavior, 2021)

Sea Urchins Play an Increasingly Important Role for Coral Resilience Across Reefs in Taiwan - Viet D. H. Dang; Pak-Yin Cheung; Chia-Ling Fong; Aziz J. Mulla; Jia-Ho Shiu; Che-Hung Lin; Yoko Nozawa (Frontiers in Marine Science, 2020)
Herbivores are an important functional group that control algae, create new space, and promote recruitment for coral recovery. However, on many coral reefs, overfishing has greatly decreased the density of herbivores, especially fishes and gastropods, impairing coral resilience. On such overfished reefs, remnant herbivores that are not target species of local fisheries, e.g., sea urchins, are expected to play an increasingly important role, yet few studies, except for those in the Caribbean and Kenya have examined non-fish herbivores in relation to coral resilience. Here, we conducted field surveys at 30 sites along three coral reefs in Taiwan between 2016 and 2017, to examine the relative importance of six key factors for coral resilience: herbivore abundance (fishes, gastropods, sea urchins), coral cover, macroalgal cover, habitat complexity, water depth, and wave exposure. The density of juvenile coral was used as a proxy of coral resilience. Diadematid sea urchins ( Echinothrix spp. and Diadema spp.) dominated most sites (19 of 30 sites) and multivariable regression models showed sea urchin density as the best positive predictor of coral juvenile density. The results elucidated the increasing role diadematid sea urchins play as remnant herbivores on overfished coral reefs in Taiwan. Given that overfishing is a widespread issue, this phenomenon may be occurring globally. More studies are needed to examine the role of remnant, but often ignored, sea urchin herbivory on coral resilience. Reef managers should consider monitoring locally remnant herbivores and incorporating them into management strategies.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Noise exposure assessment and prevention around high-speed rail - K.-T. Tsai; M.-D. Lin; Y.-H. Lin (International Journal of Environmental Science and Technology, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Endocrine-Disrupting Activities and Organic Contaminants Associated with Oil and Gas Operations in Wyoming Groundwater - Christopher D. Kassotis; Danh C. Vu; Phuc H. Vo; Chung-Ho Lin; Jennifer N. Cornelius-Green; Sharyle Patton; Susan C. Nagel (Archives of Environmental Contamination and Toxicology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Optical types of inland and coastal waters - Evangelos Spyrakos; Ruth O'Donnell; Peter D. Hunter; Claire Miller; Marian Scott; Stefan G. H. Simis; Claire Neil; Claudio C. F. Barbosa; Caren E. Binding; Shane Bradt; Mariano Bresciani; Giorgio Dall'Olmo; et al. (Limnology and Oceanography, 2018)
Inland and coastal waterbodies are critical components of the global biosphere. Timely monitoring is necessary to enhance our understanding of their functions, the drivers impacting on these functions and to deliver more effective management. The ability to observe waterbodies from space has led to Earth observation (EO) becoming established as an important source of information on water quality and ecosystem condition. However, progress toward a globally valid EO approach is still largely hampered by inconsistences over temporally and spatially variable in‐water optical conditions. In this study, a comprehensive dataset from more than 250 aquatic systems, representing a wide range of conditions, was analyzed in order to develop a typology of optical water types (OWTs) for inland and coastal waters. We introduce a novel approach for clustering in situ hyperspectral water reflectance measurements ( n = 4045) from multiple sources based on a functional data analysis. The resulting classification algorithm identified 13 spectrally distinct clusters of measurements in inland waters, and a further nine clusters from the marine environment. The distinction and characterization of OWTs was supported by the availability of a wide range of coincident data on biogeochemical and inherent optical properties from inland waters. Phylogenetic trees based on the shapes of cluster means were constructed to identify similarities among the derived clusters with respect to spectral diversity. This typification provides a valuable framework for a globally applicable EO scheme and the design of future EO missions.

Development of a two-stage washing and biodegradation system to remediate octachlorinated dibenzo-p-dioxin-contaminated soils - J. L. Lin; C. D. Dong; C. W. Chen; S. H. Chen; T. E. Hsieh; C. M. Kao (International Journal of Environmental Science and Technology, 2017)

Cardiotoxicity Associated with Nicotinamide Phosphoribosyltransferase Inhibitors in Rodents and in Rat and Human-Derived Cells Lines - D. L. Misner; M. A. Kauss; J. Singh; H. Uppal; A. Bruening-Wright; B. M. Liederer; T. Lin; B. McCray; N. La; T. Nguyen; D. Sampath; P. S. Dragovich; et al. (Cardiovascular Toxicology, 2017)

The genus Fusariella - Chuan-Gen Lin; Yun Chen; Eric H. C. McKenzie; Darbhe J. Bhat; Hiran A. Ariyawansa; Kevin D. Hyde; Yong Wang (Mycological Progress, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Differentiation in development of benzimidazole resistance in Colletotrichum gloeosporioides complex populations from strawberry and grape hosts - T. Lin; X. F. Xu; D. J. Dai; H. J. Shi; H. D. Wang; C. Q. Zhang (Australasian Plant Pathology, 2016)

Biogeographic patterns of soil diazotrophic communities across six forests in the North America - Qichao Tu; Ye Deng; Qingyun Yan; Lina Shen; Lu Lin; Zhili He; Liyou Wu; Joy D. Van Nostrand; Vanessa Buzzard; Sean T. Michaletz; Brian J. Enquist; Michael D. Weiser; et al. (Molecular Ecology, 2016)
Soil diazotrophs play important roles in ecosystem functioning by converting atmospheric N 2 into biologically available ammonium. However, the diversity and distribution of soil diazotrophic communities in different forests and whether they follow biogeographic patterns similar to macroorganisms still remain unclear. By sequencing nifH gene amplicons, we surveyed the diversity, structure and biogeographic patterns of soil diazotrophic communities across six North American forests (126 nested samples). Our results showed that each forest harboured markedly different soil diazotrophic communities and that these communities followed traditional biogeographic patterns similar to plant and animal communities, including the taxa–area relationship ( TAR ) and latitudinal diversity gradient. Significantly higher community diversity and lower microbial spatial turnover rates (i.e. z ‐values) were found for rainforests (~0.06) than temperate forests (~0.1). The gradient pattern of TAR s and community diversity was strongly correlated ( r 2 > 0.5) with latitude, annual mean temperature, plant species richness and precipitation, and weakly correlated ( r 2 pH and soil moisture. This study suggests that even microbial subcommunities (e.g. soil diazotrophs) follow general biogeographic patterns (e.g. TAR , latitudinal diversity gradient), and indicates that the metabolic theory of ecology and habitat heterogeneity may be the major underlying ecological mechanisms shaping the biogeographic patterns of soil diazotrophic communities.

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Diversity and degradation mechanism of an anaerobic bacterial community treating phenolic wastewater with sulfate as an electron acceptor - X. J. Guo; Z. Y. Lu; P. Wang; H. Li; Z. Z. Huang; K. F. Lin; Y. D. Liu (Environmental Science and Pollution Research, 2015)

Overexpression of AT14A confers tolerance to drought stress-induced oxidative damage in suspension cultured cells of Arabidopsis thaliana - Lin Wang; Jie He; Haidong Ding; Hui Liu; Bing Lü; Jiansheng Liang; L. Wang; J. He; H. D. Ding; H. Liu; B. Lü; J. S. Liang (Protoplasma, 2015)

Survival among Black and White patients with renal cell carcinoma in an equal-access health care system - Jie Lin; Shelia H. Zahm; Craig D. Shriver; Mark Purdue; Katherine A. McGlynn; Kangmin Zhu (Cancer Causes & Control, 2015)

Association between plasma adiponectin levels and colorectal cancer risk in women - Paulette D. Chandler; Julie E. Buring; JoAnn E. Manson; M. V. Moorthy; Shumin Zhang; I-Min Lee; Jennifer H. Lin (Cancer Causes & Control, 2015)

Mass mortality associated with a viral‐induced anaemia in cage‐reared large yellow croaker, Larimichthys crocea (Richardson) - W J Xu; Z D Qin; H Shi; N Jiang; Y Zhou; X L Liu; J J Xie; G S Wang; W M Wang; M Asim; L B Zeng; L Lin (Journal of Fish Diseases, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Anti-tuberculosis treatments and risk of hepatocellular carcinoma in tuberculosis patients with liver cirrhosis: a population-based case–control study - Y.-P. Lim; C.-L. Lin; D.-Z. Hung; Y.-N. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Accumulation of arsenic in rice plant: a study of an arsenic-contaminated site in Taiwan - S.-C. Lin; T.-K. Chang; W.-D. Huang; H.-S. Lur; G.-S. Shyu (Paddy and Water Environment, 2015)

Trends in the susceptibility of commonly encountered clinically significant anaerobes and susceptibilities of blood isolates of anaerobes to 16 antimicrobial agents, including fidaxomicin and rifaximin, 2008–2012, northern Taiwan - F. D. Wang; C. H. Liao; Y. T. Lin; W. H. Sheng; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

On the origin of water-soluble organic tracer compounds in fine aerosols in two cities: the case of Los Angeles and Barcelona - M. Alier; M. Dall Osto; Y.-H. Lin; J. D. Surratt; R. Tauler; J. O. Grimalt; B. L. van Drooge (Environmental Science and Pollution Research, 2014)

Clinical and microbiological characteristics of Klebsiella pneumoniae from community-acquired recurrent urinary tract infections - W. H. Lin; C. Y. Kao; D. C. Yang; C. C. Tseng; A. B. Wu; C. H. Teng; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Evaluation of seedling resistance of rice germplasm resources to sheath blight (Rhizoctonia solani) - B. Chen; L.-W. Li; Y.-J. Lin; Z.-H. Wang; G.-D. Lu (Cereal Research Communications, 2014)

Erratum to: Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Erratum to: Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Preladenant, a selective adenosine A2A receptor antagonist, is not associated with QT/QTc prolongation - Z. Wang; F. Xuan; W. H. Lin; M. D. Troyer; A. Tendolkar; D. L. Cutler (European Journal of Clinical Pharmacology, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2013)

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Metabolic imaging of mild traumatic brain injury - A. P. Lin; H. J. Liao; S. K. Merugumala; S. P. Prabhu; W. P. Meehan; B. D. Ross (Brain Imaging and Behavior, 2012)

Regional economic impact analysis of earthquakes in northern Taiwan and its implications for disaster reduction policies - H. C. Lin; Y. L. Kuo; D. Shaw; M. C. Chang; T. M. Kao (Natural Hazards, 2012)

Germ cells and fertilization differences among Japanese flounder Paralichthys olivaceus , summer flounder Paralichthys dentatus and their first and second generations - J. Sui; D. Y. Ma; Q. H. Liu; S. H. Xu; Z. Z. Xiao; F. Lin; Y. S. Xiao; J. Li (Journal of Fish Biology, 2012)
The morphology of gametes and the fertilization biology of Japanese flounder Paralichthys olivaceus (Po), summer flounder Paralichthys dentatus (Pd) and their hybrids were examined. Multiple generations (two hybrids: Po♀× Pd♂ (F1) and Pd♀× Po♂; two backcrosses: F1♀× Po♂ and F1♀× Pd♂) were obtained by artificial insemination. Comparison of egg ultrastructure among Po, Pd and F1 showed the morphology of micropyle region and the distribution density of pores were species specific. There were c . 100–200 accessory openings around the micropyle in Po, but not in Pd and F1. The zona radiata thickness and number of parallel bands were similar between F1 and Po, which were different from Pd. Comparison of spermatozoa ultrastructure revealed a close relationship between Po and Pd. Cytologically, the six crosses obeyed normal fertilization and cleavage processes, and only one male pronucleus was observed in a fertilized egg, indicating a monospermic fertilization pattern. Analysis of the time distribution from fertilization to first cleavage revealed an obvious delay at pronucleus fusion in the Pd × Po cross. The delay might indicate some cytoplasmic‐nuclear incompatibility during the process of fertilization.

Three new species of Lentinus from northern Thailand - Samantha C. Karunarathna; Zhu L. Yang; Rui-Lin Zhao; Else C. Vellinga; A. H. Bahkali; Ekachai Chukeatirote; Kevin D. Hyde (Mycological Progress, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Multiple factors have shaped the phylogeography of Chinese spiny loach Cobitis sinensis in Taiwan as inferred from mitochondrial DNA variation - T.‐Y. Chiang; H.‐D. Lin; K.‐T. Shao; K.‐C. Hsu (Journal of Fish Biology, 2010)
Mitochondrial DNA cytochrome b sequences (1140 bp) in 61 specimens of Chinese spiny loach Cobitis sinensis from 12 drainages in Taiwan were identified as two major clades, exhibiting a southern and a northern distribution, north of TzengWen and south of TzengWen (including TzengWen), respectively. The divergence time between these two phylogroups was estimated at 7·34–9·06 million years before present ( b.p. ), but these two phylogroups were formed c. 3·41–4·23 and 2·22–2·75 M b.p. , respectively. Moreover, geological events have been recalculated that Taiwan Island emerged above sea level at an estimate of c . 4–5 M b.p. , and quickly became its present shape at c. 2 M b.p. through mountain building. These results suggest that these two major clades of C. sinensis in Taiwan might originate from two different continental populations, since the island's initial isolation in the Pliocene. Within southern Taiwan, the initial colonization was hypothesized to be in KaoPing River, followed by its northward dispersal. The high divergence between KaoPing and TzengWen was influenced by glaciations and landforms. Within north Taiwan, the colonization was from the Miaoli Plateau through western Taiwan to north‐eastern and northern Taiwan. This dispersal pattern is concordant with the previously proposed hypothesis. Apparently, both geological and phylogeographic evidence suggested that river capture of the upper Takia River by the LanYang River promoted range expansion in freshwater fishes and also indicated that the Central Range within Taiwan did not act as a barrier to the dispersal of C. sinensis .

Effects of two species of inorganic arsenic on the nutrient physiology of rice seedlings - Hai Bin Wang; H. B. He; G. D. Yang; C. Y. Ye; B. H. Niu; W. X. Lin (Acta Physiologiae Plantarum, 2010)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

The importance of myocardial amino acids during ischemia and reperfusion in dilated left ventricle of patients with degenerative mitral valve disease - A. Venturini; R. Ascione; H. Lin; E. Polesel; G. D. Angelini; M.-S. Suleiman (Molecular and Cellular Biochemistry, 2009)

Treatment of polluted river water by a gravel contact oxidation system constructed under riverbed - D. F. Juang; W. P. Tsai; W. K. Liu; J. H. Lin (International Journal of Environmental Science and Technology, 2008)

Sensitivity of future ozone concentrations in the northeast USA to regional climate change - K. E. Kunkel; H.-C. Huang; X.-Z. Liang; J.-T. Lin; D. Wuebbles; Z. Tao; A. Williams; M. Caughey; J. Zhu; K. Hayhoe (Mitigation and Adaptation Strategies for Global Change, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Scaling and organization of electroencephalographic background activity and alpha rhythm in healthy young adults - D. C. Lin; A. Sharif; H. C. Kwan (Biological Cybernetics, 2006)

Isolation and Characterization of Two Phenol-Degrading Yeast Strains from Marine Sediment - Z. Hu; Y. R. Wu; B. K. Lin; K. Maskaoui; D. H. Zhuang; T. L. Zheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Potential Volatile Organic Compound Exposure from Dry Process Photocopiers in Operation-Idle Mode - D.-J. Hsu; H.-L. Huang; H.-Y. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Nucleotide sequence and mRNA expression analysis of β-actin gene in the orange-spotted grouper Epinephelus coioides - W. M. Zhang; Y. Zhang; L. H. Zhang; S. G. Wang; T. Y. Zhu; D. Lin; G. Z. Ma (Fish Physiology and Biochemistry, 2005)

Potential Exposure to VOCs Caused by Dry Process Photocopiers: Results From a Chamber Study - D.-J. Hsu; H.-L. Huang; C.-H. Chien; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419נWangshuibai population. I. TypeII resistance - F. Lin; Z. X. Kong; H. L. Zhu; S. L. Xue; J. Z. Wu; D. G. Tian; J. B. Wei; C. Q. Zhang; Z. Q. Ma (Theoretical and Applied Genetics, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Kinetic Studies on the Effects of Organophosphorus Pesticides on the Growth of Microcystis aeruginosa and Uptake of the Phosphorus Forms - P.-J. Zhou; H. Shen; J. Lin; L.-R. Song; Y.-D. Liu; Z.-B. Wu (Bulletin of Environmental Contamination and Toxicology, 2004)

Kinetic Studies on the Combined Effects of Lanthanum and Cerium on the Growth of Microcystis aeruginosa and their Accumulation by M. aeruginosa - P.-J. Zhou; J. Lin; H. Shen; T. Li; L.-R. Song; Y.-W. Shen; Y.-D. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

QTLs for Na+ and K+ uptake of the shoots and roots controlling rice salt tolerance - H. X. Lin; M. Z. Zhu; M. Yano; J. P. Gao; Z. W. Liang; W. A. Su; X. H. Hu; Z. H. Ren; D. Y. Chao (Theoretical and Applied Genetics, 2004)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Yield Surface of Mu-San Sandstone by Hollow Cylinder Tests - D.-H. Lee; C. H. Juang; H.-M. Lin (Rock Mechanics and Rock Engineering, 2002)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Agricultural Chemicals in the Alluvial Aquifer of a Typical County of the Arkansas Delta - H. S. Lin; H. D. Scott; K. F. Steele; H. I. Inyang (Environmental Monitoring and Assessment, 1999)

Probing Transmembrane Topology of the High-Affinity Sodium/Glucose Cotransporter (SGLT1) with Histidine-Tagged Mutants - J.-T. Lin; J. Kormanec; D. Homerová; R.K.-H. Kinne (The Journal of Membrane Biology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

G6PD Toronto - J. H. Crookston; A. Yoshida; M. Lin; D. J. Booser (Biochemical Genetics, 1973)